2022
DOI: 10.1038/s41370-022-00512-y
|View full text |Cite
|
Sign up to set email alerts
|

Linking environmental injustices in Detroit, MI to institutional racial segregation through historical federal redlining

Abstract: Objectives To identify the most pervasive environmental exposures driving environmental disparities today associated with historical redlining in Detroit. Methods We overlaid Detroit’s 1939 Home Owners’ Loan Corporation (HOLC) shapefile from the Mapping Inequality project onto the EPA EJScreen and the DOT National Transportation Noise maps to analyze differences in current demographic and environmental indicators between historically redlined (D-grade) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Redlining persisted across the United States from 1933 to 1968 in over 230 cities. , Alongside restrictive deeds, racialized zoning, steering, and social violence, redlining led to land use and decision making that worsened the environmental quality for redlined neighborhoods. ,, In this study, we assessed 868 previously HOLC-graded neighborhoods across eight California cities and found that redlining is strongly associated with environmental quality. Our results enrich the redlining literature by demonstrating that formerly redlined neighborhoods exhibit significantly poorer environmental quality than other HOLC grades, including less investigated hazards such as noise pollution, lead, and contaminated water. This holds implications for human health disparities, as redlined neighborhoods in California are composed of census tracts with higher proportions of Hispanic and Black populations, as well as a people living in poverty, than greenlined neighborhoods . Our results shed light on the enduring, far-reaching impact of redlining, a policy that was abolished almost 60 years ago, on contemporary environmental quality.…”
Section: Discussionsupporting
confidence: 63%
“…Redlining persisted across the United States from 1933 to 1968 in over 230 cities. , Alongside restrictive deeds, racialized zoning, steering, and social violence, redlining led to land use and decision making that worsened the environmental quality for redlined neighborhoods. ,, In this study, we assessed 868 previously HOLC-graded neighborhoods across eight California cities and found that redlining is strongly associated with environmental quality. Our results enrich the redlining literature by demonstrating that formerly redlined neighborhoods exhibit significantly poorer environmental quality than other HOLC grades, including less investigated hazards such as noise pollution, lead, and contaminated water. This holds implications for human health disparities, as redlined neighborhoods in California are composed of census tracts with higher proportions of Hispanic and Black populations, as well as a people living in poverty, than greenlined neighborhoods . Our results shed light on the enduring, far-reaching impact of redlining, a policy that was abolished almost 60 years ago, on contemporary environmental quality.…”
Section: Discussionsupporting
confidence: 63%
“…However, proximity to major roadways also reflects a complex and intersecting socio‐economic and neighbourhood‐level factor. For example, historical redlining in Detroit (a racist housing practice implemented in the United States throughout the 1900s), resulted in 12% higher PM and 32% larger traffic volumes for individuals living in redlined as compared with non‐redlined neighbourhoods 27 . This work highlights how individuals that live close to major roadways are more likely to have low SES or to be from a minoritized community.…”
Section: Figurementioning
confidence: 87%
“…For example, historical redlining in Detroit (a racist housing practice implemented in the United States throughout the 1900s), resulted in 12% higher PM and 32% larger traffic volumes for individuals living in redlined as compared with non-redlined neighbourhoods. 27 This work highlights how individuals that live close to major roadways are more likely to have low SES or to be from a minoritized community. Subsequently, these individuals bear disproportionate pollution exposures and related morbidity burdens, emphasizing the need to consider socio-economic factors when evaluating pollution impacts in clinical populations.…”
mentioning
confidence: 99%
“…32,[36][37][38] For example, mortgage lending bias has resulted in residential segregation and underinvestment in some communities, with inequities in wealth accumulated across generations. [39][40][41] Residential segregation has been associated with poorer living environments, including higher exposure to ambient air pollution or other environmental pollutants, [42][43][44][45] and higher risk of late-stage cancer diagnosis, poorer survival, and higher cancer mortality. 39,40,[46][47][48][49] Social determinants of health could positively or negatively affect cancer occurrence through their effects on educational and job 5); e.g., the proportion of people aged 18-64 years who did not own a house was about twice as high among Black people (55.3%) as among White people (28.2%).…”
Section: Social Determinants Of Healthmentioning
confidence: 99%
“…For example, mortgage lending bias has resulted in residential segregation and underinvestment in some communities, with inequities in wealth accumulated across generations 39–41 . Residential segregation has been associated with poorer living environments, including higher exposure to ambient air pollution or other environmental pollutants, 42–45 and higher risk of late‐stage cancer diagnosis, poorer survival, and higher cancer mortality 39,40,46–49 …”
Section: Factors Contributing To Cancer Disparitiesmentioning
confidence: 99%